Teaching STEAM in the shaolin staff program: ways to stimulate student engagement in learning - Chen, Haidong; Rao, Feixue; Chen, Ran; Lin, Zhaowei (Frontiers in Psychology, 2023)
With the advancement of technology and change in education concepts, applying STEAM pedagogy to physical education has become an innovative trend. This study investigates whether physics analysis based on STEAM concepts can increase junior high students' participation in learning Shaolin Staff. Forty students were randomly assigned to experimental and control groups. The mean and standard deviation of age in the experimental group was 13.95±0.83, and in the control group was 13.85±0.81. The experimental group received STEAM teaching involving physics analysis, while the control group received conventional movement instruction. Student learning engagement was evaluated through questionnaires. Results are expected to show the experimental group being more engaged in learning. Introducing physics analysis may deepen understanding of related principles to movements. The study's results found that the scores of motivation, attention, and intention to learn independently were significantly higher in the experimental group than in the control group (p<0.01). The scores of interfering emotions were significantly lower in the experimental group than in the control group (p<0.01), which verified that the STEAM teaching method could effectively improve learning engagement. This study promotes STEAM education in martial arts and provides insights on utilizing STEAM to boost student engagement.